Police Officer-Civilian Confrontations Caught on Camera: the Influence of Contextual Frames on Judgements of Excessive Force - Baker, Melissa A. (American journal of criminal justice, 2017)
In the present studies, participants viewed a brief staged video of a physical confrontation between a police officer and a civilian. Participants were then asked if the police officer had used excessive force. When people view videos of police officer-civilian confrontations, their judgements concerning the use of excessive force by officers are likely constrained by various framing factors. Our studies were designed to investigate the effects of two different contextual frames on participants’ judgements of police officer use of excessive force. 1) We investigated how informational frames accompanying a confrontation video, might frame judgments about use of excessive force, and 2) we investigated how demographic frames , or demographic characteristics, might frame judgments of excessive force. In Study 1, an informational frame warned participants that the confrontation video captured a very brief segment of an event that transpired over a longer period of time. In Study 2, the video was accompanied with an informational frame in which a rationale for the activity of the police officer was explained. Police officer gender was experimentally manipulated in both studies: participants saw a video of either a female or a male police officer affecting an arrest. Participant demographic information was also collected. Logistic regression analysis showed that judgments of excessive force were related to participant demographic characteristics but not to police officer gender. The informational frames appeared to have no effect on excessive force judgments. The results have implications for future research regarding the types of factors that frame people’s judgments of the use of force by police officers when watching police officer-civilian confrontation videos. The results also have implications for efforts to provide a context for these types of videos when they appear in television news programs.